PALEOENVIRONMENTAL CONSTRAINTS ON PLEISTOCENE ICE SHEETS FROM GLACIO-VOLCANIC DEPOSITS IN NORTHEAST ICELAND - (:unkn) unknown (My University, 2024)
There are indications that the melt-back of glaciers due to climate change can trigger new eruptions for volcanoes and magma reservoirs that rest under ice sheets. The ideal locality on Earth to study volcano-ice interactions is Iceland, an active volcanic island that has been totally covered in previous ice ages. Eruptions under glaciers produce distinctive landforms called tuyas, or table mountains, which can provide an estimate of ice thickness at the time of eruption. One research tool used to investigate ice thickness is volcanic glass, which is formed from rapid cooling of magma, and thus is abundant in the majority of systems where eruptions occur under or within ice or glacial meltwater. In particular, northeast Iceland has been used as a yardstick for ice thickness estimates using tuyas based on the elevation of capping lava flows and glassy eruptive products, and previous research suggests that ice thickness increases to the south towards Iceland’s largest, present-day glacier: Vatnajökull. We hypothesize that ice thickness estimates using volatiles in volcanic glass record a similar story of ice thickness for northeast Iceland, with ice thickness increasing to the south for tuyas closer to Vatnajökull glacier. We report some of the first chemical data for volcanic glasses including water, carbon dioxide, major elements, and sulfur concentrations for four tuyas in northeast Iceland: Gæsafjöll, Búrfell, Bláfjall, and Herðubreið. Major elements and sulfur were analyzed, and the composition of glass for all four tuyas is basaltic, suggesting their formation was due to partial melting of the mantle. However, Búrfell contains a component enriched in FeO and depleted in MgO and CaO, which may be due to different mantle sources or interaction with crystal mushes in tiered sill-like magma reservoirs. Furthermore, Búrfell shows the highest sulfur contents compared to the other three tuyas, suggesting it had more pressure exerted by overlying ice during its formation. Lastly, water content was collected using Fourier Transform Infrared Spectroscopy (FTIR). These data show that low water contents dominate for Gæsafjöll, Herðubreið, and Bláfjall suggesting thin ice during an eruption, and slightly higher water contents for Búrfell suggesting thicker ice during an eruption, which shows ice thickness did not progressively increase to the south towards Vatnajökull glacier and was more complex than previously thought. Hydrogen isotopes (D) and water contents reveal volcanic glass in northeast Iceland was a result of open system degassing based on Raleigh fractionation curves, and low water contents and D values for all four tuyas suggest substantial amounts of water have been lost during degassing. Therefore, this implies that the measured D values are not those of the original, undegassed parental magmas due to open system processes.
Keywords: Iceland; Igneous petrology; Paleoclimate; Tuya; Volatiles; Volcanic glass